Traditional Akan Ethics and Humanist Ethics: A Comparative Study - Appiah-Sekyere, Paul (Advances in Social Sciences Research Journal, 2016)
Since Traditional Akans are Africans, one can logically deduce that the former share in the notorious religiosity that characterize the later. This notwithstanding, it seems that religion is not the sole determinant of the ethics of the Akan people even though it is a sine qua non factor/source of Akan ethics. In addition to religion, the Akan Tradition is an important determinant of Akan ethics. Similar to Akan ethics, Humanist ethics is based on human reason, intellect and the experience of human society but unlike Akan ethics, Humanist ethics debunks religion and any supernaturalism. This study examines Akan ethics and Humanist ethics endeavouring to unravel how two different ethics can have many similar moral values despite differences in their respective sources.